A systematic literature review on the role of glial cells in the pathomechanisms of migraine - Zhang, Shanshan; Azubuine, Justin; Schmeer, Christian (Frontiers in Molecular Neuroscience, 2023)
The pathomechanisms underlying migraine are intricate and remain largely unclear. Initially regarded as a neuronal disorder, migraine research primarily concentrated on understanding the pathophysiological changes within neurons. However, recent advances have revealed the significant involvement of neuroinflammation and the neuro-glio-vascular interplay in migraine pathogenesis.A systematic search was conducted in PubMed, Scopus, and Web of Science databases from their inception until November 2022. The retrieved results underwent a screening process based on title and abstract, and the full texts of the remaining papers were thoroughly assessed for eligibility. Only studies that met the predetermined inclusion criteria were included in the review.Fifty-nine studies, consisting of 6 human studies and 53 animal research studies, met the inclusion criteria. Among the 6 human studies, 2 focused on genetic analyses, while the remaining studies employed functional imaging, serum analyses, and clinical trials. Regarding the 53 animal research studies investigating glial cells in migraine, 19 of them explored the role of satellite glial cells and/or Schwann cells in the trigeminal ganglion and/or trigeminal nerve. Additionally, 17 studies highlighted the significance of microglia and/or astrocytes in the trigeminal nucleus caudalis, particularly in relation to central sensitization during migraine chronification. Furthermore, 17 studies examined the involvement of astrocytes and/or microglia in the cortex.Glial cells, including astrocytes, microglia, satellite glial cells and Schwann cells in the central and peripheral nervous system, participate both in the development as well as chronic progression of migraine, in disease-associated regions such as the trigeminovascular system, trigeminal nucleus caudalis and cortex, among other brain regions.